Sedimentação e hidrodinâmica em uma praia de macromaré: Ajuruteua, Pará - CORDOVIL, Paula Eliane Pagliarini (2010)
Many classifications to coastal environments had been proposed over the years. By morphological, sedimentary and hydrodynamics analysis, is possible to classify recent depositional environments according the dominant coastal process. This work had as purpose to analyze the hydrodynamic and sedimentary pattern of Ajuruteua Beach in order to classify it in relation to depositional environment. It had been realized works of field in 2009, during the rainy seasons (March and April) and dry (September and November), where it realize topographic survey, sedimentary collection and peels obtainment in spring low tide conditions and hydrodynamic data collection (wave, current and tide). Ajuruteua Beach responded to seasonal hydrodynamic variations presenting differentiated morphology between rainy and dry seasons. During dry season, along of beach was observed sediment loss of intertidal zone and sediment addition of supratidal zone and, only at NW sector, was generated a ridge and runnel system, at raining season, the both sectors had regular and similar morphology. It was observed, that in both sectors of beach, the sediments presented similar granulometric characteristics, with mean grain size of fine sand, fluctuating of 2,64 Φ to 2,61 Φ of rainy season to dry, well sorting, of 0,48 Φ throughout the year and positive skewness fluctuating of 0,2 Φ to 0,17 Φ of rainy season to dry. In the peels was found six sedimentary facies, where was observed presence of wave generated structures during rainy and dry seasons and absence of tide generated structures. so, it concluded that throughout the year the waves are important environment moulder agents, but due to importance of local tidal range, Ajuruteua Beach can be classified as a type 1 of Short macrotidal beach, as a mixed energy environment, included in the category "meso/macrotidal beach" of coastal classification used in this work.